(untitled) (Journal of Economic Research & Business Administration, 2020)
One of the main factors limiting innovative development is the lack of funding for research activities, accompanied by low efficiency in the use of financial resources in the scientific sector. Innovative companies in the early phase of their development, for the most part, do not attract the interest of professional investors. Without proper financial support, they stagnate or close at the initial stage of formation. These companies have very limited opportunities to choose financial instruments and attract the required amount of investment, as they are usually characterized by low financial stability and limited creditworthiness, as well as a high risk of bankruptcy and lack of assets necessary for collateral (Sagiyeva, 2019:4). The high financing risks inherent in innovative entrepreneurship can be minimized by using alternative financing methods used in foreign practice. The purpose of this article is to identify factors that affect the effectiveness of the innovations financing system in Kazakhstan and develop recommendations for improving the effectiveness of such system. In the course of the research, methods of statistical data analysis and SWOT analysis of the innovations financing system in the Republic of Kazakhstan were applied. As a result of the conducted research, such key factors that affect the effectiveness of innovations financing system were identified as: weak connection between science and production, bureaucracy and inflexibility of administrative and state structures, insufficient effectiveness of the research grant funding mechanism. Recommendations were made to improve the efficiency of innovations financing.